Educação escolar quilombola: currículo, cultura, fazeres e saberes tradicionais no ensino de química - Santos, Marciano Alves dos (2018)
Quilombola School Education has gained prominence in recent years, mainly as of Resolution No. 8 of November 20, 2012, which "Defines the National Curricular Guidelines for Quilombola School Education". This work is configured as a participant research, therefore, a research designed for social transformation in which researcher and community intervene together in a demand of the community itself. In this sense, the objective was to discuss the following question: how can traditional knowledge and practices interact with the teaching of chemistry in Quilombola School Education? To answer this question, we developed a work in quilombola communities in the state of Goiás and Tocantins, first collecting information from the local Griffins and then planning pedagogical interventions for the Teaching of Chemistry in Quilombola School Education. Our results showed that it is possible to link traditional knowledge and Chemistry Teaching, enabling them to be valued at the same time as students take ownership of school scientific knowledge. Thus, there is an urgent need to train teachers and chemistry teachers to develop in Quilombola School Education a teaching work that displaces the curriculum in order to include other knowledge that dialogue with the non- universal subject.